Long shadows - Baldacci, David (New York : Grand Central Publishing, 2022)
"When Amos Decker is called to South Florida to investigate a double homicide, the case appears straightforward: A federal judge and her bodyguard have been found dead, the judge$1 (Bs face sporting a blindfold with two eye holes crudely cut out, a clear sign that she$1 (Bd made one too many enemies over her years on the bench. Decker must contend with a series of unsettling changes, including a new partner$1 (BSpecial Agent Frederica (3z(BFreddie(3y (BWhite$1 (Band a devastating event that brings Decker$1 (Bs own tragic past back to the present . . .s
Keywords: Decker, Amos -- (Fictitious character) -- Fiction; Government investigators -- Fiction; Murder -- Investigation -- Fiction; Florida -- Fiction; Large type books; Novels; Detective and mystery fiction; Thrillers (fiction).